Complete genome sequences of nine mycobacteriophages - Franceschelli, Jorgelina Judith (2014)
Genome analyses of a large number of mycobacteriophages, bacterial viruses that infect members of the genus Mycobacterium, yielded novel enzymes and tools for the genetic manipulation of mycobacteria. We report here the complete genome sequences of nine mycobacteriophages, including a new singleton, isolated using Mycobacterium smegmatis mc(2)155 as a host strain.